Autoimmune Progesterone Dermatitis: A Case Report - Rachana George; Shawky Z. A. Badawy (Case Reports in Obstetrics and Gynecology)
Background. Autoimmune progesterone dermatitis is a rare cyclic premenstrual allergic reaction to progesterone produced during the luteal phase of a woman's menstrual cycle. Patients present with a variety of conditions including erythema multiforme, eczema, urticaria, angioedema, and progesterone-induced anaphylaxis. Case. Thirty-eight-year-old woman G2P2002 presents with erythema multiforme and urticarial rash one week prior to her menses starting one year after menarche. She was treated with oral contraceptive pills and the symptoms resolved. Conclusion. This is a typical case of progesterone autoimmunity. The diagnosis is based on cyclic nature of the dermatitis. This differentiates the condition from other allergies or systemic diseases with skin manifestations. Inhibition of ovulation in such cases results in decrease in progesterone secretion and prevention of symptoms.